2018
DOI: 10.5005/jp-journals-10024-2215
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antimicrobial Therapy after Extraction of Impacted Mandibular Third Molar: A Randomized Clinical Trial

Abstract: Aim: The present study was conducted with the aim of evaluating the effectiveness of antimicrobial therapy following extraction of an impacted mandibular third molar. Materials and methods:This randomized controlled trial was conducted on a total of 60 patients who were randomly assigned into three groups: Group I individuals were given 625 mg of combined amoxicillin and clavulanic acid tablet; 625 mg of combined amoxicillin and clavulanic acid tablet + 400 mg metronidazole tablet was given to group II individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Furthermore, at T2 the number of patients reporting pain decreased dramatically in all the groups, whose mean NRS value was close to 0. This finding confirms that complications after tooth extraction are generally mild and self‐limiting (Lodi et al., 2012; Rabi et al., 2018; Simon & Matee, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, at T2 the number of patients reporting pain decreased dramatically in all the groups, whose mean NRS value was close to 0. This finding confirms that complications after tooth extraction are generally mild and self‐limiting (Lodi et al., 2012; Rabi et al., 2018; Simon & Matee, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…This in turn depends on various factors such as age of the patient, amount of bone removal, difficulty of extraction, surgeon's experience, pre-existing infection, duration and technique of extraction. 5,[21][22][23] The general pattern of post-operative pain, regardless of antimicrobial use in the present study had shown that the pain was severely maximum on POD 1 which decreased on POD 3 and became nil at POD 7 . Pain score on POD 7 was lower in patients of Azithromycin group compared to Amoxicillin group which was statistically significant.…”
Section: Discussionmentioning
confidence: 71%
“…Common significant post-operative complications associated with the extractive surgery requiring bone removal are pain, trismus, swelling and infection. 1,2,5 In dentistry, Amoxicillin is the common drug used for the treatment and prevention of infections. However, the development of resistance to this drug has become common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two RCTs were included as narrative in the systematic review [ 20 , 21 ]. Fourteen RCTs were included in the meta-analysis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%